Value Leakage in Product-Service System Provision : A Business Model Alignment Perspective - Reim, Wiebke; Lenka, Sambit; Parida, Vinit; Frishammar, Johan (IEEE, 2022)
To stay competitive, manufacturing companies offer product–service systems (PSS) to avoid commoditization of their products. The potential to create value through PSS offerings lies in a company's ability to successfully implement the PSS business model. However, many companies are unable to realize the benefits because PSS represents significant changes to all the business model elements, which comprise value creation, value delivery, and value capture. This leads to misalignment among the business model elements, which is a topic of interest within PSS and business model literatures. This article aims to provide empirical insights into the business-model-element alignment problems and conceptualize their consequences, which manufacturing companies face during PSS implementation. This article utilizes an abductive multicase study of three Swedish manufacturing companies with long-term experience of PSS provision to provide novel insights by identifying six alignment problems that companies face as a consequence of the interaction among the three business model elements. Furthermore, we contribute to both the PSS and business model literature by conceptualizing the consequences of business model element alignment problems, explaining the three value leakages that occur as a result of inappropriate resource and capability utilization, unattractive offer configurations, and inefficient service network processes in PSS provision.
Keywords: Advanced services; alignment; business model; Companies; Context modeling; Encoding; Faces; Interviews; Manufacturing; product-service systems (PSS); servitization; value destruction; value leakage; business; fi=Strateginen johtaminen|en=Strategic Management|